Pengembangan Pancake Pangan Fungsional Berbasis Nutrisi Vitamin dari Spirulina, Kedelai, dan Beras Merah (NUTRIVITA-SKB) untuk Dukungan Gizi Anak - Mahanani, Amalia Jati; Maharani, Cakra; Sarbini, Dwi (Dinasti Research, 2026)
The development of functional pancake (NUTRIVITA-SKB) based on spirulina, soybean, and red rice for child nutritional support is motivated by the high prevalence of stunting and malnutrition among children in Indonesia. This study aimed to develop a functional food product in the form of pancake and to evaluate its physical quality, sensory attributes, and nutritional content. The study used three formulations tested through color analysis, moisture content determination, sensory evaluation by 15 panelists, and nutrient calculation including energy, protein, fat, carbohydrate, and dietary fiber. The results showed that the third formulation had the brightest color with lightness value of 39.45, redness of 25.8, and yellowness of 16.85, the lowest moisture content of 20.96 percent, and the highest energy and protein content of 491.8 kilocalories and 25.2 grams. Meanwhile, the first formulation obtained the highest organoleptic scores in taste, aroma, texture, and overall acceptability. The nutritional profiles of all formulations indicate strong potential to meet children's energy and protein requirements. The third formulation is more suitable for nutritional support, while the first formulation is more acceptable to consumers. Therefore, NUTRIVITA-SKB pancake has promising potential to be developed as an innovative functional food to support child nutrition.